Effectiveness evaluation of antibiotic use in patients with Methicillin-resistant Staphylococcus aureus (MRSA) infection: a review - As, Musdalifa; Ika Puspitasari; Nuryastuti, Titik (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogen that become a public health problem due to its ability to be resistant to more than three classes of antibiotics. Evaluation of the effectiveness of antibiotic use in patients with MRSA is important to optimize antibiotic use and to control antibiotic resistance. This article review attempted to evaluate the effectiveness of antibiotics in patients with MRSA. This review explored the results of previous research from PubMed as a literature source and the PRISMA flow diagram as a protocol for the article selection process. Eight studies reviewed the evaluation of the effectiveness of antibiotic use in MRSA patients with various clinical conditions, such as uncomplicated wound infections, cellulitis and no wound, purulent drainage or abscess, cSSSI infections caused by MRSA, infections caused by MRSA bacteremia and nosocomial infections caused by MRSA. In conclusion, the effectiveness of antibiotics in patients with MRSA infection depends on the clinical condition of each patient. Therefore, the use of antibiotics is adjusted based on the type of infection and the efficacy of the antibiotics. Combination therapy is recommended for MRSA patients considering its life-threatening ability.